The impact of digital intelligence on energy-intensive firms’ green transformation - Mengge Hao; Feng Zhang; Shichun Xu; Zhixin Dong; Zhengxia He (Environmental Research Communications)
The green transformation of energy-intensive firms is expected to make an outstanding contribution to global carbon neutrality. Digital intelligence, the new phase of digitalization, has injected fresh momentum into corporate green development. Most previous studies focused on the green effect of digitalization using statistical data from listed firms, and failed to make detailed exploration on the impact of digital intelligence on energy-intensive firms’ green transformation based on survey data. Based on empowerment theory and technology-organization-environment theory, this study proposed a three-dimensional concept of digital intelligence, including digital intelligence technology, digital intelligence organization and digital intelligence environment. Using survey data from 348 energy-intensive firms in China, this paper employed the structural equation modeling and bootstrap test to investigate the influence of digital intelligence on energy efficiency transformation and green emission transformation, and the mediating effect of energy management. The results indicate that digital intelligence technology, digital intelligence organization and digital intelligence environment promote energy efficiency and green emission of energy-intensive firms. Energy management is the key to the green transformation of energy-intensive firms in the context of digital intelligence. Specifically, energy saving literacy, energy audit, and energy use structure optimization play the positive mediating effects between digital intelligence and energy-intensive firms’ green transformation. It is worth noting that the mediating effect of energy saving literacy between digital intelligence environment and energy-intensive firms’ green transformation is insignificant. These findings provide policy and practice references for the government and practitioners in energy-intensive industries to leverage digital intelligence to promote green sustainability.